2016
DOI: 10.1016/j.bbrc.2016.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Induced differentiation inhibits sphere formation in neuroblastoma

Abstract: Neuroblastoma arises from the neural crest, the precursor cells of the sympathoadrenal axis, and differentiation status is a key prognostic factor used for clinical risk group stratification and treatment strategies. Neuroblastoma tumor-initiating cells have been successfully isolated from patient tumor samples and bone marrow using sphere culture, which is well established to promote growth of neural crest stem cells. However, accurate quantification of sphere-forming frequency of commonly used neuroblastoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Cells were plated onto an ultra-low attachment 96-well plate at serial dilutions. Each well was scored for presence of sphere formation as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were plated onto an ultra-low attachment 96-well plate at serial dilutions. Each well was scored for presence of sphere formation as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Investigators have shown that activation of RAR/RXR receptors upregulated transcription of genes involved in differentiation [ 53 ], and downregulated transcription of genes responsible for generation and maintenance of SCLCCs [ 54 ]. In preclinical studies, RA was reported to reduce stemness characteristics in various tumors including neuroblastoma [ 55 ]. Despite the clinical effectiveness of RA therapy for some neuroblastoma patients with minimal residual disease, there are still many high-risk and advanced neuroblastoma patients with tumors that do not respond to RA [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…N-MYC promotes a stem-like state by impairing the differentiation pathways and supporting self-renewal and pluripotency. N-MYC-amplified neuroblastoma cell lines, including BE(2)-C cells, form spheres more frequently than non-N-MYC-amplified cell lines and sphere formation is sensitive to cellular differentiation status [ 32 ]. In the present study, BE(2)-C sphere formation was reduced and associated with cell death after EGCG and IIF treatments.…”
Section: Discussionmentioning
confidence: 99%